ΤΟ ΣΤΑΔΙΟ ΤΗΣ ΕΡΕΥΝΑΣ ΣΧΕΤΙΚΑ ΜΕ ΤΗΝ ΕΛΛΗΝΙΚΗ ΕΜΠΟΡΙΚΗ ΔΙΑΣΠΟΡΑ ΣΤΟΝ ΡΟΥΜΑΝΙΚΟ ΧΩΡΟ (ΤΟΝ 17ο - 18ο ΑΙΩΝΑ) - CICANCI, OLGA (Eoa kai Esperia, 2007)
This paper offers an overview of the state of research on the Greek tradediaspora in Romania. The preoccupation of the Romanian historiographywith the Greek trade diaspora in Romania dates back to early 40’s. The commercialactivity and the institutional organization of the Greek tradecompanies of Sibiu and Braçov was the topic which initially attracted theattention of Romanian historians. Since the 80’s multiplied the number ofpublications and research projects concerning the history of Greek merchanthouses in the Transylvanian towns, while the economic role of Greeks hasbeen accentuated by scholars of the Romanian economic history of the 18thcentury. Recently, the research interest has been expanded to the study of theGreek commercial activity in the Romanian port-cities during the 19thcentury. The paper includes information about archival data, unpublisheddocuments and doctoral theses, as well as a list of the more recentpublications concerning the history of the Greek trade diaspora in Romania.